Bitcoin and blockchain : history and current applications - Panda, Sandeep Kumar, 1985-; Elngar, Ahmed A.; Balas, Valentina Emilia; Kayed, Mohammed (Boca Raton, FL : CRC Press, 2020)
In recent years, blockchain development has grown quickly from the original Bitcoin protocol to the second-generation Ethereum platform, and to today's process of building third-generation blockchains. During this evolution, we can see how blockchain technology has evolved from its original form as a distributed database to becoming a fully fledged, globally distributed, cloud computing platform. This book traces the past, present, and future of blockchain technology. Presents the knowledge and history of Bitcoin Offers blockchain applications Discusses developing working code for real-world blockchain applications Includes many real-life examples Covers the original Bitcoin protocol to the second-generation Ethereum platform Bitcoin and Blockchain: History and Current Applications is a useful reference for students, business schools, research scholars, practitioners, and business analytics professionals.
Chapter 1. Bitcoin: A P2P Digital Currency. Chapter 2. Exploring the Bitcoin Network. Chapter 3. Blockchain Technology: The Trust-Free Systems. Chapter 4. Consensus and Mining in a Nutshell. Chapter 5. Blockchain: Introduction to the Technology behind Shared Information. Chapter 6. Growth of Financial Transaction toward Bitcoin and Blockchain Technology. Chapter 7. A Brief Overview of Blockchain Algorighm and Its Impact upon Cloud-Connected Environment. Chapter 8. Solidity Essentials. Chapter 9. Installing Frameworks, Deploying, and Testing Smart Contracts in Ethereum Platform. Chapter 10. Blockchain in Healthcare Sector. Chapter 11. Blockchain Theories and Its Applications. Chapter 12. Building Permissioned Blockchain Networks Using Hyperledger Fabric. Chapter 13. Fraud-Resistant Crowdfunding System Using Ethereum Blockchain.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Bitcoin; COMPUTERS / Reference